2009
DOI: 10.1039/b807061j
|View full text |Cite
|
Sign up to set email alerts
|

Consensus multivariate methods in gas chromatography mass spectrometry and denaturing gradient gel electrophoresis: MHC-congenic and other strains of mice can be classified according to the profiles of volatiles and microflora in their scent-marks

Abstract: House mice (Mus domesticus) communicate using scent-marks, and the chemical and microbial composition of these 'extended phenotypes' are both influenced by genetics. This study examined how the genes of the major histocompatibility complex (MHC) and background genes influence the volatile compounds (analysed with Gas Chromatography Mass Spectrometry or GC/MS) and microbial communities (analysed using Denaturating Gradient Gel Electrophoresis or DGGE) in scent-marks produced by congenic strains of mice. The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Here we found that the structures of the bacterial and VFA profiles of hyena pastes strongly covaried. Prior studies using microbial fingerprinting surveys revealed that the bacterial and odor profiles of human axillae covaried among people who adhered to presampling guidelines on bathing and deodorant use (34) and that the bacterial and odor profiles of the urine-marks of laboratory mouse strains, Mus domesticus, were partially correlated (35). The current study focused on wild populations of mammals, and showed strong, consistent covariance between the bacterial and odor profiles of mammalian scent gland secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Here we found that the structures of the bacterial and VFA profiles of hyena pastes strongly covaried. Prior studies using microbial fingerprinting surveys revealed that the bacterial and odor profiles of human axillae covaried among people who adhered to presampling guidelines on bathing and deodorant use (34) and that the bacterial and odor profiles of the urine-marks of laboratory mouse strains, Mus domesticus, were partially correlated (35). The current study focused on wild populations of mammals, and showed strong, consistent covariance between the bacterial and odor profiles of mammalian scent gland secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zomer et al (2009) investigated the profiles of volatile compounds and microorganisms associated with the scent-marks collected from two BALB MHCcongenic strains and two B10 MHC-congenic strains. Since the volatile profiles of the real scent-marks were highly variable, urine samples (labelled as 'simulated scent-marks') were used for the chemical analyses.…”
Section: Chemical Investigations Of Mhc Odourtype In Micementioning
confidence: 99%
“…To evaluate this conjecture, several groups examined the urinary volatile profiles of MHC-congenic mice derived from different background strains (Eggert et al 1996;Willse et al 2006;Novotny et al 2007;Zomer et al 2009). Eggert et al (1996) investigated the urinary volatile metabolic profiles of BALB/c (H2 d ), BALB/k (H2 k ) and C3H (H2 k ) mice.…”
Section: Chemical Investigations Of Mhc Odourtype In Micementioning
confidence: 99%
“…Differences in MHC-ligand binding efficiency can influence markers used in MHC-type recognition either by restricting different excreted peptide sequences [27,45] or by selecting the microbial biota associated with individuals [46][47][48]. The peptide-binding groove of MHC molecules generates a pool of 9-mer peptides cleaved from longer protein sequences.…”
Section: Discussionmentioning
confidence: 99%